2015
DOI: 10.1186/s12866-015-0597-z
|View full text |Cite
|
Sign up to set email alerts
|

Molecular epidemiology of carbapenem resistant Enterobacteriaceae in Valle d’Aosta region, Italy, shows the emergence of KPC-2 producing Klebsiella pneumoniae clonal complex 101 (ST101 and ST1789)

Abstract: BackgroundThe spread of carbapenem resistant Enterobacteriaceae (CRE) is an emerging clinical problem, of great relevance in Europe and worldwide. The aim of this study was the molecular epidemiology of CRE isolates in Valle d’Aosta region, Italy, and the mechanism of carbapenem resistance.ResultsSixty consecutive CRE samples were isolated from 52 hospital inpatients and/or outpatients from November 2013 to August 2014. Genotyping of microbial isolates was done by pulsed-field gel electrophoresis (PFGE) and mu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
60
2
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 65 publications
(67 citation statements)
references
References 43 publications
4
60
2
1
Order By: Relevance
“…In our study we were for the first time able to detect this Balkan NDM-1 outside a medical setting [15,5962]. The detected NDM-1 harboring Klebsiella pneumoniae ST101 is also associated with carbapenem resistant Klebsiella in the Mediterranean region, but this resistance is mediated via KPC-2 and OXA-48 [50,63]. …”
Section: Discussionmentioning
confidence: 99%
“…In our study we were for the first time able to detect this Balkan NDM-1 outside a medical setting [15,5962]. The detected NDM-1 harboring Klebsiella pneumoniae ST101 is also associated with carbapenem resistant Klebsiella in the Mediterranean region, but this resistance is mediated via KPC-2 and OXA-48 [50,63]. …”
Section: Discussionmentioning
confidence: 99%
“…A retroactive study on colistin-resistant Enterobacteriaceae isolates obtained from January 2013 to November 2015 at a hospital in China found two K. pneumoniae harboring mcr-1 and bla NDM-5 [Du 2016]. Four bla KPC-2 producing K. pneumoniae ST101 from a cohort of nosocomial CRE obtained in Italy from November 2013 to August 2014 had colistin resistance (MIC 16–125 μg/ml) through an unidentified mechanism [Del Franco 2015]. …”
Section: Contribution Of Carbapenemases To Mdr/xdr Enterobacteriaceaementioning
confidence: 99%
“…bla has been commonly associated with ST101 worldwide and, according to the results of an 11-year (2001 to 2011) molecular epidemiologic study of bla in Europe and North Africa, ST101 is the most frequently observed sequence type (13). Among the carbapenem-resistant K. pneumoniae STs identified in this study, the emergence of colistin resistance had been already reported in KPC-2-producing ST101 (14) and bla KPC-2 -and bla CTX-M -producing ST307 (15,16). Carbapenem-and colistin-resistant isolates of ST437 have been reported previously (17).…”
mentioning
confidence: 94%